Evaluation of UDP-based reliable transport protocols in wireless network / Madzirin Masirap - Masirap, Madzirin (2014)
This paper is mainly interested in near real-time wireless application with regards to Internet of Things (IoT). Wireless network speed had been improved significantly since its introduction. We had seen its wide implementations in various sectors. This however doesn't dismiss the fact that wireless network is unreliable. Its unreliability comes from various sources such as wireless signal collision and hardware issue. The idea of wireless networking is interesting mainly because it introduce portability. For IoT application that require near real-time wireless connection, the traditional TCP protocol is not suitable because of its packet header size and its conservative Additive Increase Multiplicative Decrease (AIMD) congestion control algorithm and slow start strategy. This paper mainly evaluates three kinds of UDP-based high speed transport protocols (RUBDP, UDT, and PA-UDP). The evaluation was done on a test bed that consist of two machine connected by wireless ad-hoc network. This paper focused on the effect of data size by monitoring throughput of the implemented protocol. This paper also discussed the CPU behavior on the sender and receiver side of each protocol. The paper findings are, PA-UDP protocol has the best transport performance but it requires high CPU utilization during the start and end of transmission at the receiver side. UDT protocol is most efficient in term of CPU usage but jt has lesser throughput. RBUDP performed consistently in wireless network but the CPU usage is very high at the sender side. The conclusion drawn on this paper is UDT protocol is most suitable protocol for IoT because it has consistent performance and CPU friendly.